Influence of Grapevine Leafroll-associated Virus-3 in Mature Plants of Vitis vinifera L. cv Albariño on 110R and 196.17C Rootstocks - Cabaleiro, C.; Pesqueira, A.M.; García-Berrios, Julián Jesús (South African Journal of Enology and Viticulture, 2021)
The detrimental effects of grapevine leafroll disease (GLD) have been documented mainly in young plants and little data is available on infected grapevines when they reach maturity. This study examined the influence of the rootstock on the effect of GLRaV-3 in a 20-year-old Vitis vinifera cv Albariño vineyard in which the virus has been spread by Planococcus ficus. Plants grafted on Richter 110 or Castell 196.17 with similar development were analysed for grapevine leafroll-associated viruses. In particular, 25 GLRaV-3- infected and 25 leafroll-free and asymptomatic vines were selected and monitored during a period of three years to determine grape yield and must components. Although the virus infection affected plants on both rootstocks, it caused a greater effect on plants grafted onto 110R, with average accumulated yield losses of up to 33%, relative to losses of 16% for plants on 196.17C. The sugar content was lower in the must from infected plants on 110R (-2.1ºBrix) than in the must from plants on 196.17C (-1.5ºBrix). The presence of the virus was associated with decreased concentrations of primary amino nitrogen (PAN) and ammonium (NH4+), with the greatest effect for 110R (-35%). As 110R is the most used rootstock in Spain, particular care must be taken to prevent the transmission of GLRaV-3 to certified virus-free plants on 110R in new vineyards. In sensitive varieties such as Albariño, particularly in areas with an active spread of the virus by mealybugs, grafting on 196.17C seems to minimise the effect that GLD has in a medium to long term.